Economic and Technical Feasibility of Grain Chilling in Brazil - Lopes, Daniela de Carvalho; Steidle Neto, Antonio José (Journal of Basic & Applied Sciences, 2021)
Grain quality is critical due to the more stringent food-safety demands. Chilled aeration has become a popular technology for preventing grain spoilage during storage, mainly in warmer regions. However, a limiting factor in broad-scale adoption of chilling is the general belief that this technology is much more expensive than other post-harvest methods, such as the aeration with ambient air. In this work, ambient and chilled aeration were simulated considering the three major grain-producing regions in Brazil. Also, three storage capacities (95, 5000, 10500 t), five-grain types (corn, coffee, rice, bean, soybean), and two storage periods (beginning at the first and the last months of the harvest period) were used in the study, totalling 180 simulation scenarios. Based on these simulations a comparative cash flow analysis was performed aiming at evaluating the influence of the product, storage period, region, and silo size on the costs and profits from using these technologies. Results were strongly affected by the weather patterns of the studied regions, market values of grain, storage sizes, and fan operation hours. Chilled aeration should be economically competitive with ambient aeration, and the two technologies appeared as low-risk investments in Brazil, achieving average profits for 20 years by considering the time of money of US$ 68 and 59.4 million, respectively. Considering the technical factors, chilling presented higher energy consumption, but showed a greater potential for reducing grain temperatures and resulted in grain dry matter losses around 58% smaller than those verified when using ambient air.